Associative interplay of Pseudomonas gessardii BLP141 and pressmud ameliorated growth, physiology, yield, and Pb-toxicity in sunflower. Issue 2 (3rd April 2021) - Raza Altaf, Adnan; Teng, Haipeng; Saleem, Muhammad; Raza Ahmad, Hamaad; Adil, Muhammad; Shahzad, Khurram
Abstract: Lead is getting more and more alarming because of its toxicity and destructive effects on plants, animals, and human health. The higher lead uptake by plants deteriorate the consistency in growth and yield of crops. However, plant growth-promoting rhizobacteria (PGPR) interacting with the organic matter could be a practical approach to ameliorate the Pb toxicity. Therefore, the current study was planned to investigate the combined effect of organic matter with PGPR on the growth, physiology, and yield of sunflower plants in the lead polluted soil. For this purpose, the soil was contaminated (600 mg kg −1 ) by Pb (NO3 )2 salt solution and composted with pressmud 2% (w/w) as an organic amendment; sunflower seeds were inoculated with a lead tolerant bacterial strain ( Pseudomonas gessardii BLP141). Composted soil samples were collected from un-inoculated and unpolluted treatment to investigate the Physico-chemical variations in soil. After harvesting, agronomical data (growth, yield, physiology) was recorded, and plant tissues (root, shoot, and achene) were analyzed for Pb contents. Results revealed that the combined application had significantly improved the plant growth (65%), total chlorophyll contents (63%), yield (47%), and lead immobilization (78%) over lead control in lead polluted soil. The soil organic matter (26%), total nitrogen contents (21%), available phosphorus (20%), and extractable potassium contents (26%) were improved in pressmud control after the 105 days of the first incubation period. Through this feasible practice, the plant growth and yield of sunflower can be enhanced, and soil could be managed from lead toxicity.